2018
DOI: 10.3390/ph11040126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Boswellia Serrata Roxb. and Curcuma longa L. in an In Vitro Intestinal Inflammation Model Using Immune Cells and Caco-2

Abstract: Inflammatory bowel diseases, which consist of chronic inflammatory conditions of the colon and the small intestine, are considered a global disease of our modern society. Recently, the interest toward the use of herbal therapies for the management of inflammatory bowel diseases has increased because of their effectiveness and favourable safety profile, compared to conventional drugs. Boswellia serrata Roxb. and Curcuma longa L. are amongst the most promising herbal drugs, however, their clinical use in inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 89 publications
0
19
0
1
Order By: Relevance
“…e mentioned action was also observed in an in vitro model of intestinal inflammation. Besides it, the protective effect of turmeric on the intestinal epithelium may be promising for patients with inflammatory bowel disease [78]. Also, it has been shown that turmeric significantly lowers the level of high-sensitivity C-reactive protein (as an acute-phase protein) in a number of clinical trials [79,80].…”
Section: Antioxidant and Anti-inflammatory Activitymentioning
confidence: 99%
“…e mentioned action was also observed in an in vitro model of intestinal inflammation. Besides it, the protective effect of turmeric on the intestinal epithelium may be promising for patients with inflammatory bowel disease [78]. Also, it has been shown that turmeric significantly lowers the level of high-sensitivity C-reactive protein (as an acute-phase protein) in a number of clinical trials [79,80].…”
Section: Antioxidant and Anti-inflammatory Activitymentioning
confidence: 99%
“…The efficiency of the barrier functions was evaluated by measuring trans-epithelial electric resistance (TEER) using a voltmeter [36]. Caco-2 cells (8 × 10 5 ) were placed in transparent polyester membrane cell culture inserts with 0.4 µM pore size (Sarstedt) as previously described [37]. Culture medium was replaced every other day.…”
Section: Measurement Of Trans-epithelial Electric Resistancementioning
confidence: 99%
“…In IBDs, patients upregulated expression of cytokines (such as TNF-α, IL-6, IL-12, IL-17) and substance P [25,26], and alterations in gut microbiota [27] were observed, as well as significantly increased numbers of mast cells in the mucosa of the ileum and colon [28], even in IBS patients [29]. Mast cells play a very important role in the regulation of intestinal permeability and, being below the intestinal mucosa barrier, can be activated by microbial antigens [30,31]. In addition, levels of tight junction proteins are significantly downregulated in IBDs patients, leading to increased gut permeability to microbial ligands and noxious metabolites, resulting in systemic inflammatory responses [32,33].…”
Section: Introductionmentioning
confidence: 99%